A review on pregnancy after intestinal transplantation. (17th January 2017) - Lauro, Augusto; Matsumoto, Cal S.; Marino, Ignazio R.; Berghella, Vincenzo
Abstract: The largest experience of pregnancy after solid organ transplantation is recorded in renal and liver recipients. Intestinal/multivisceral transplantation has shown steady improvements in graft and patient survival over the past 20 years and is rapidly becoming more established: the first pregnancy after this procedure was described 10 years ago, and so far eight cases of pregnancies with 100% successful live births have been reported worldwide. Specifically to this procedure, there are 2 factors to be considered in case of pregnancy: absorptive function of transplanted bowel and higher need of immune-suppressants. Close monitoring of renal function and of the graft by endoscopies and biopsies can be considered during the pregnancy to prevent episodes of rejection or enteritis, preserving the fetus by temporary malnutrition. As more intestinal transplant patients are surviving and regaining reproductive function, it is important to report this option to female recipients and to their health-care professionals.